Neuroanatomical and neurocognitive changes associated with subjective cognitive decline - Rivas-Fernández, Miguel Ángel; Lindín, Mónica; Zurrón, Montserrat; Díaz, Fernando; Lojo-Seoane, Cristina; Pereiro, Arturo X.; Galdo-Álvarez, Santiago (Frontiers in Medicine, 2023)
Introduction Subjective Cognitive Decline (SCD) can progress to mild cognitive impairment (MCI) and Alzheimer’s disease (AD) dementia and thus may represent a preclinical stage of the AD continuum. However, evidence about structural changes observed in the brain during SCD remains inconsistent. Materials and methods This cross-sectional study aimed to evaluate, in subjects recruited from the CompAS project, neurocognitive and neurostructural differences between a group of forty-nine control subjects and forty-nine individuals who met the diagnostic criteria for SCD and exhibited high levels of subjective cognitive complaints (SCCs). Structural magnetic resonance imaging was used to compare neuroanatomical differences in brain volume and cortical thickness between both groups. Results Relative to the control group, the SCD group displayed structural changes involving frontal, parietal, and medial temporal lobe regions of critical importance in AD etiology and functionally related to several cognitive domains, including executive control, attention, memory, and language. Conclusion Despite the absence of clinical deficits, SCD may constitute a preclinical entity with a similar (although subtle) pattern of neuroanatomical changes to that observed in individuals with amnestic MCI or AD dementia.